2021
DOI: 10.5382/econgeo.4793
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate Replacement as the Principal Ore Formation Process in the Proterozoic McArthur River (HYC) Sediment-Hosted Zn-Pb Deposit, Australia

Abstract: The McArthur River (HYC) Zn-Pb-Ag deposit in the Carpentaria Zn belt, northern Australia, is one of the world’s largest and most studied sediment-hosted base metal deposits, owing to its lack of deformation and preservation of sedimentary and ore textures. However, the ore formation process (syngenetic vs. epigenetic) is still a subject of controversy. In this paper we focus on key characteristics of the HYC deposit that remain unexplained: preservation of sedimentary carbonate (dolomite) and its association w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 56 publications
(136 reference statements)
4
24
0
Order By: Relevance
“…The modeling results show that a simple mixing of Zn-bearing (∼1000 ppm Zn) brines with H 2 S of as much as 0.2 m under acid or near-neutral pH conditions would not effectively precipitate sphalerite at 150-250 °C. This is because the partial precipitation of sphalerite decreases the fluid pH and stops the ore deposition due to the high solubility of sphalerite in acidic solutions, as shown in Cooke et al (2000) and Spinks et al (2021). The much higher degree of galena precipitation in the carbonate-free experiments is due to the lower solubility of galena compared to sphalerite (e.g., Etschmann et al, 2018).…”
Section: Role Of Carbonatesmentioning
confidence: 87%
See 1 more Smart Citation
“…The modeling results show that a simple mixing of Zn-bearing (∼1000 ppm Zn) brines with H 2 S of as much as 0.2 m under acid or near-neutral pH conditions would not effectively precipitate sphalerite at 150-250 °C. This is because the partial precipitation of sphalerite decreases the fluid pH and stops the ore deposition due to the high solubility of sphalerite in acidic solutions, as shown in Cooke et al (2000) and Spinks et al (2021). The much higher degree of galena precipitation in the carbonate-free experiments is due to the lower solubility of galena compared to sphalerite (e.g., Etschmann et al, 2018).…”
Section: Role Of Carbonatesmentioning
confidence: 87%
“…Sediment-hosted Zn-Pb deposits, such as Mississippi Valley-type (MVT), Irish-type, and sedimentary exhalative (SEDEX) (e.g., Large et al, 2005;Leach et al, 2005;Wilkinson, 2014), are the most important Zn and Pb resources globally. Different ore-genesis models have been proposed for different classes of these deposits: Large et al (1998Large et al ( , 2005 proposed a syn-sedimentary-exhalative origin for the giant HYC deposits (McArthur River, Australia), while Perkins and Bell (1998) and Spinks et al (2021) identified key features of post-sedimentary mineralization and carbonate replacement by metal sulfide minerals. A carbonate replacement model is proposed for the Irish-type (e.g., Wilkinson, 2014;Wilkinson and Hitzman, 2015) and MVT-type deposits (e.g., Corbella et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…There has been considerable debate over the sulfide paragenesis at the McArthur River (HYC) deposit, and specifically the relative timing of fine-grained diagenetic pyrite and sphalerite mineralization (summarized by Large et al, 1998). For example, previous researchers either favor models in which the bulk of the Zn mineralization is syn-py1, consistent with a SEDEX model (e.g., Large et al, 1998;Ireland et al, 2004) or post-py1, which is consistent with subseafloor replacement (Williams, 1978;Eldridge et al, 1993;Spinks et al, 2021).…”
Section: Geology Of the Teena And Mcarthur River (Hyc) Depositsmentioning
confidence: 99%
“…Using this reference value there is no evidence of carbonate loss, yet it does not preclude the possibility that the interbedded siltstones are unmineralized precisely because of a lack of preexisting nodular carbonate. Indeed, recent work on the ore zone at the McArthur River (HYC) deposit has now provided more convincing petrographic evidence of widespread sulfide replacement of carbonate (Spinks et al, 2021).…”
Section: The Chemical Mass Balance Of Dolomite Replacement Sulfide Mineralization In the Lower Hyc Unitmentioning
confidence: 99%
See 1 more Smart Citation